Correlation Between Foot Posture and Genu Valgum Incidence in Children Aged 9 – 12 Years in Elementary Schools Throughout Denpasar - Putu Ayu Wulan Purnama Dewi; Anak Ayu Nyoman Trisna Narta Dewi; Ni Komang Ayu Juni Antari; Agung Wiwiek Indrayani (Bali Anatomy Journal, 2020)
Background: Pronated foot posture to over pronated foot posture are an indication of the incidence of genu valgum which is a deformity of the lower limbs where the soles of the feet are pronated and far from each other while the knees are in a close position until they are attached. Children at the age of three to eight years will experience genu valgum physiologically. Aim: The purpose of this study was to find out the general description and to prove the correlation between foot posture and the incidence of genu valgum in elementary schools children throughout Denpasar. Methods: This study was an analytic observation method with cross-sectional study design with total sample was 77 participants and used simple random sampling method. This study was conducted from January to February 2020 at 18th Pemecutan Elementary School, 26th Dangin Puri Elementary School, 9th Sesetan Elementary School, and 10th Dauh Puri Elementary School. Results: The results showed out of 77 samples analyzed, concluded 45 (58.4%) male and 32 (41.6%) female participants. There were 37 (48.1%) participants indicated genu valgum and 40 (51.9%) participants with normal foot. Total were 36 participants indicated with pronated foot posture and 41 participants with normal foot posture. Based on the Mann-Whitney U test results obtained p value of the left and right foot posture of <0.001 which means there is a correlation between the left and right foot with incidence of genu valgum. Conclusion: This study concluded that there is a correlation between foot posture and the incidence of genu valgum in elementary schools children throughout Denpasar.